Prison elite : how Austrian Chancellor Kurt Schuschnigg survived Nazi captivity - Rummel, Erika, 1942- (Toronto ; Buffalo ; London : University of Toronto Press, 2021)
"After the Anschluss (annexation) in 1938, the Nazis forced Austrian Chancellor Kurt Schuschnigg to resign and kept him imprisoned for seven years, until his rescue by the Allies in 1945. Schuschnigg's privileged position within the concentration camp system allowed him to keep a diary and to write letters which were smuggled out to family members. Drawing on these records, Prison Elite paints a picture of a little-known aspect of concentration camp history: the life of a VIP prisoner. Schuschnigg, who was a devout Catholic, presents his memoirs as a "confession," expecting absolution for any political missteps and, more specifically, for his dictatorial regime in the 1930s. As Erika Rummel reveals in fascinating detail, his autobiographical writings are frequently unreliable. Prison Elite describes the strategies Schuschnigg used to survive his captivity emotionally and intellectually. Religion, memory of better days, friendship, books and music, and maintaining a sense of humour allowed him to cope. A comparison with the memoirs of fellow captives reveals these tactics to be universal. Studying Schuschnigg's writing in the context of contemporary prison memoirs, Prison Elite provides unique insight into the life of a VIP prisoner"--
1. In isolation : living under the enemy's eye -- 2. The Sachsenhausen household : living en famille -- 3. The comfort of religion -- 4. The consolation of books -- 5. Music to his ears -- 6. The use of wit -- 7. Cherishing memories -- 8. Schuschnigg's political reminiscences.
Includes bibliographical references and index.
Erika Rummel is a professor emerita in the Department of History at Wilfrid Laurier University.
Print version record.
JSTOR
Keywords: Schuschnigg, Kurt, -- 1897-1977.; Sachsenhausen (Concentration camp); Schuschnigg, Kurt, -- 1897-1977; Sachsenhausen (Concentration camp); Statesmen -- Austria -- Biography; Statesmen -- Austria -- Diaries; Statesmen -- Austria -- Correspondence; World War, 1939-1945 -- Prisoners and prisons, German -- Biography; World War, 1939-1945 -- Prisoners and prisons, German -- Diaries; World War, 1939-1945 -- Prisoners and prisons, German -- Correspondence; World War, 1939-1945 -- Concentration camps; Hommes d'État -- Autriche -- Biographies; Hommes d'État -- Autriche -- Journaux intimes; Hommes d'État -- Autriche -- Correspondance; Guerre mondiale, 1939-1945 -- Prisonniers et prisons des Allemands -- Biographies; Guerre mondiale, 1939-1945 -- Prisonniers et prisons des Allemands -- Journaux intimes; Guerre mondiale, 1939-1945 -- Prisonniers et prisons des Allemands -- Correspondance; Guerre mondiale, 1939-1945 -- Camps d'internement.; HISTORY / Europe / Austria & Hungary; Internment camps; Statesmen; Austria; 1939-1945; Biography; Biographies; Diaries; Personal correspondence; Biographies; Biographies